Association between recent U.S. northeast precipitation trends and Greenland blocking - Julia M. Simonson; Sean D. Birkel; Kirk A. Maasch; Paul A. Mayewski; Bradfield Lyon; Andrew M. Carleton (International Journal of Climatology, 2022)
Since the early 2000s, the northeastern region of the United States (USNE) has received increased total annual precipitation along with more frequent extreme precipitation events. Although previous work has discussed the contribution to increased extreme precipitation from tropical cyclones, the large‐scale driver(s) of summer precipitation increases in the extratropics has received little attention. Here, we show that the summer‐season rainfall surpluses across the USNE are related to the increased frequency of atmospheric blocking over Greenland and the negative phase of the North Atlantic Oscillation. The occurrence of these patterns in summer has been previously connected with southward shifted storm tracks and wet conditions across the eastern North Atlantic. Over the USNE, the circulation shifts are also related to enhanced rainfall due to southerly wind anomalies and increased moisture transport into and vertical motion over the region. It is important to note that the current generation of climate models used for future projections is unable to reproduce the observed tendency towards increased atmospheric blocking over Greenland. Thus, clarifying the association between Greenland blocking and recent precipitation changes across the USNE may help inform future climate projections of summer season rainfall for the region.

A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Ian D. Goodwin; Stuart Browning; Andrew M. Lorrey; Paul A. Mayewski; Steven J. Phipps; Nancy A. N. Bertler; Ross P. Edwards; Tim J. Cohen; Tas van Ommen; Mark Curran; Cameron Barr; J. Curt Stager (Climate Dynamics, 2014)

An ice‐core proxy for northerly air mass incursions into West Antarctica - Daniel A. Dixon; Paul A. Mayewski; Ian D. Goodwin; Gareth J. Marshall; Rhaelene Freeman; Kirk A. Maasch; Sharon B. Sneed (International Journal of Climatology, 2012)
A 200‐year proxy for northerly air mass incursions (NAMI) into central and western West Antarctica is developed from the examination of 19 shallow (21–150 m deep) Antarctic ice‐core non‐sea‐salt (nss) Ca 2+ concentration records. The NAMI proxy reveals a significant rise in recent decades. This rise is unprecedented for at least the past 200 years and is coincident with anthropogenically driven changes in other large‐scale Southern Hemisphere (SH) environmental phenomena such as greenhouse gas (GHG) induced warming, ozone depletion, and the associated intensification of the SH westerlies. The Hysplit trajectory model is used to examine air mass transport pathways into West Antarctica. Empirical orthogonal function analysis, in combination with trajectory results, suggests that atmospheric circulation is the dominant factor affecting nssCa 2+ concentrations throughout central and western West Antarctica. Ozone recovery will likely weaken the spring‐summer SH westerlies in the future. Consequently, Antarctica could lose one of its best defences against SH GHG warming. Copyright © 2011 Royal Meteorological Society

Variability of Sea-Ice Extent in Baffin Bay over the Last Millennium - Nancy S. Grumet; Cameron P. Wake; Paul A. Mayewski; Gregory A. Zielinski; Sallie I. Whitlow; Roy M. Koerner; David A. Fisher; James M. Woollett (Climatic Change, 2001)

Fresh snow chemistry from high mountain regions in central himalayas - Shi-chang Kang; Da-he Qin; Tan-dong Yao; A. Mayewski Paul; Whitlow Sallie (Chinese Geographical Science, 2000)

Precipitation fluctuations in the Nepal Himalaya and its vicinity and relationship with some large scale climatological parameters - Arun B. Shrestha; Cameron P. Wake; Jack E. Dibb; Paul A. Mayewski (International Journal of Climatology, 2000)